Una finestra sul passato: Irse de casa di Carmen Martín Gaite (Altre Modernità, 2015)
Beyond historical and social implications, migration represents the possibility of crossing a threshold and opening oneself up to new empirical and emotional spaces. Amparo, the main character of Carmen Martín Gaite’s Irse de casa (1998), is the perfect personification of the gaitian feminine canon. After leaving Spain and settling in New York, she became a successful fashion designer, and seemed happy and easy-going. The bond with memory and the past is the main topic of this novel, as it is in most of Martín Gaite’s production. The window on the past that Amparo closed moving to the US suddenly reappears when she needs to discover herself and her origins. This inconvenience in an anonymous life brings huge changes that will condition her and her loved ones. Travelling to Spain and interacting with places and people connected with her childhood, Amparo goes through the window she had closed forty years before, restoring the order. The window connects the present and the past, symbolizes the emigrant’s transience, personified in the novel by Amparo, who can definitely find the lost serenity and heart’s-ease.